ENSURING SUSTAINABLE INNOVATIVE DEVELOPMENT OF ENTERPRISES IN THE CONDITIONS OF DIGITALIZATION - Жарков, О.О. (SWorldJournal, 2025)
The article explores the theoretical and methodological foundations and practical approaches to ensuring sustainable innovative development of enterprises in the context of digital transformation of the economy. The role of digitalization as a key factor